“Step by Step” in Camp Prose: Aleksandr Solzhenitsyn’s ”One day in the Life of Ivan Denisovich” and Imre Kertesz’s “Fatelessness” - Molnár, Angelika (Slavica, 2021)
The paper is devoted to the disclosure of the concrete and abstract images of "step(ping) " and the reinvention of related other meanings (concepts like ’path’, ’fate’and ’happiness’)in the novel by A.I. Solzhenitsyn "One Day in the Life of Ivan Denisovich" and in the novel by Imre Kertesz "Fatelessness". In order to identify the similarities and differences concerning these fundamental text-forming components in these outstanding works of camp prose, it is necessary to turn to the study of trophes, i.e. creating new meanings on the basis of the combination of incompatible things and images. This allows us to approach the author’s picture of the world in both cases.